Assessment of Carbon Pool Formation by Pure Planted Kandelia obovata Sheue, Liu & Yong Forest in the Coastal Area of Da Loc Commune, Hau Loc District, Thanh Hoa Province - Hanh, Nguyen Thi Hong; Duc, Dam Trong (VNU Journal of Science: Natural Sciences and Technology, 2017)
Assessment of carbon pool formation in the coastal mangroves that serve the greenhouse gas emissions management, providing scientific basis and information for international discussion in implementation of GHG reductions programs such as REDD, REDD+. Research showed results of the possibility of carbon pool formation of K. obovata at the ages of 18, 17, 16 years in the coastal areas of Da Loc commune, Hau Loc district, Thanh Hoa province, that based on 3 carbon pool of the forest: (1) Carbon pool in plants above the ground; (2) carbon pool in plants below ground; (3) N.T.H. Hạnh, Đ.T. Đức / Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ, Tập 33, Số 3 (2017) 14-25 carbon pool in the soil, in the organic forms of carbon following the guidance of the IPCC (2006). The results showed that the carbon accumulation ability of the forests corresponded to the amount of CO2 that increased with forest ages. The annual carbon accumulation of the 18-years-old forest reaches 19.18 tons/ha.year (equal to 70.39 tons/ha.year of CO2); following is the 17-years-old forest reaching 14.76 tons/ha.year (equal to 54.17 tons/ha.year of CO2). The lowest is the 16-years-old forest reaching 14.64 tons/ha.year (equal to 53.73 tons/ha.year of CO2). The high carbon accumulation ability of the forest is a scientific basis for the development and implementation of mangrove plantation projects, in the combination with conservation, sustainable management, and improvement of forest carbon pools in coastal areas of Vietnam.